Avaliação antimicrobiana da associação de óleo essencial de Lippia sidoides Cham. e antimicrobianos para revestimento em fio de sutura cirúrgico absorvível - Carvalho, Caroline Uchôa Souza (2022)
Bacterial resistance is considered a worldwide public health problem, occurring when health care is provided to patients. Surgical Site Infections (SSIs) are characterized by microbial infestation in wounds from surgical procedures, where the act of suturing aims to repair tissues and prevent pathogens from contaminating the site, however, it can become the source of infection itself. Among the materials used, suture threads coated with antimicrobials can reduce contamination in the surgical site, indicating that they are therapeutic options to reduce rates of wound infections. The present study aimed to develop a new coating for polyglactin suture threads, using associations of essential oil from the plant Lippia sidoides Cham. (OELS) with the antimicrobials ciprofloxacin and ampicillin. In order to obtain synergistic associations between oil and antimicrobials, the CIF Fractional Inhibitory Concentration test (checkerboard) was performed and, for the evaluation of antimicrobial activity in a bacterial biofilm model, the Crystal Violet technique was used. The associations demonstrated synergism, in addition to the ability to inhibit bacterial growth and reduce biofilm formation. The synergistic concentrations were used to produce a coating solution for polyglactin suture. The coated wire was later tested for the growth of bacterial biofilm on its surface, showing positive results in relation to the reduction of microbial growth, when compared to Vicryl Plus®, the only wire coated with an antimicrobial substance on the market today. The suture thread with OELS proved to be a therapeutic alternative for a new product with the property of reducing microbial growth and, therefore, reducing the risks of Surgical Site Infections (SSIs).